Indonesian Migrant Workers Problem in Public Sector - Syamsuddin, Syamsuddin; Utomo, Gunadi Setyo (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This study meant to identify problems faced by Indonesian migrant workers in public sector in Penang Island, Malaysia. Data gathered through closed and opened questionaires that 77 randomly choosen among migrant workers working in public sector in Penang. Data are analyzed through qualitative-descriptive technique, related to migrant workers right that finally their problem can be concluded. The result showed that problems faced by migrant workers in Penang Island were about training, accomodation, debt bandage, wage and overhour, health service and work-leave, violence, and work hour. It recommended that the Ministry of Social Affairs can improve its supervision on menpower service institution in implementing replacement process as regulated, sort of giving initial training before they go to work. Would-be migrant workers need to be given more comprehensive understanding on right and obligation as migrant workers and get information chanel for complaining if they are treated in behaviour that violate their right, and get guidance and advocation form Indonesian representative. In General Consulate of Republic of Indonesian, Penang needed social attache with international licenced professional social worker that help migrant worker facing problem.